A time asynchronous parameters calibration method of high-precision FOG-IMU based on a single-axis continuous rotation scheme. (16th February 2023) - Chang, Jiachong; Fan, Shiwei; Zhang, Ya; Li, Jingchun; Shao, Jianbo; Xu, Dingjie
Abstract: There is a time asynchronous problem with the output signals between each inertial sensor in an actual high-precision fiber optic gyro inertial measurement unit (FOG-IMU), which reduces the velocity update accuracy of the strap-down inertial navigation system in the actual applications. Firstly, the velocity error formulas are derived in the coordinate navigation system considering three time asynchronous errors between the three-axis accelerometers and gyros. Then an error-state Kalman filter is designed with respect to the time asynchronous parameters measurement model in angular dynamic environments. Afterward, a single-axis continuous rotation scheme is developed to calibrate the time asynchronous parameters. In particular, a simple observability analysis model is proposed to verify the rationality of the calibration scheme. Furthermore, the time asynchronous parameters are calculated effectively based on the proposed indirect calibration scheme. Finally, the proposed method is verified effectively through simulations and turntable experiments, which can significantly reduce the measurement errors of high-precision FOG-IMU. As a result, compared with the traditional three-parameter direct calibration method, the eastward and northward velocity errors are reduced by 7.01% and 2.48%, respectively.